The Finance-Growth Nexus: Evidence from Emerging Markets - Fanta, Ashenafi Beyene (Journal of Economics and Behavioral Studies, 2015)
The finance growth literature ignores the role of bond markets in financing private investments. Moreover, the impact of bank crisis on the finance growth link has been largely overlooked. This paper aims at casting light at the finance growth link in emerging economies by accounting for bond markets and controlling for banking sector crises. Data on economic growth and financial development indicators for 15 emerging economies (drawn from Africa, Asia, Latin America, and Europe) were analysed using a system generalized-method-of-moments (GMM) technique. It is observed that while banking sector development is related to economic growth (albeit negatively), no statistically significant relation is observed between stock markets and or bonds markets and economic growth. Moreover, a banking crisis is found to affect the finance growth link in such a manner that the link weakens when a banking crisis is introduced to the model. Our results are robust to omitted variable bias, simultaneity problem, heteroscedasticity and autocorrelation.